An analysis of indoor air temperature and relative humidity in office room with various external shading devices in Malaysia - Denan, Zuraini; Arifin, Nor Azah (Elsevier, 2015)
External shading devices have been utilized very extensively in office buildings in the tropics to reduce the amount of solar radiation entering into the buildings. In addition, the shading systems significantly improved the performance of daylighting by controlling the amount of lights levels of illumination entering into buildings. During hottest days the impact was higher; however the shading layers could still increase the amount of temperature gains through the glazing. Several methods can be employed to improve indoor thermal environment including using light colors for external surfaces, using a reflective glazing system, and using the appropriate thermal properties of external structure walls and roof. Therefore, this paper discusses the indoor temperature and relative humidity by using indoor temperature and relative humidity equipment (HOBO Data Logger) for an office room with three different types of shading devices in Malaysia, which are focusing on the vertical shading, horizontal shading and egg-crate shading. The objectives of this research are; to measure the indoor air temperature and relative humidity in the office building, to identify the highest, lowest and average indoor temperature and relative humidity in the office building, to compare with standard guideline of air temperature and relative humidity and to find out which shading is suitable to be applied in achieving thermal comfort in an office The method use in this research is field measurement. The results indicate that egg crate shading has significant impact on decreasing indoor temperature as well as discomfort hours compared with other shading types.